2017
DOI: 10.1039/c7ra04985d
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free Pd(0)/SiO2-catalyzed aminocarbonylation of aryl iodides to amides under atmospheric CO pressure

Abstract: An efficient and facile route for CO-based carbonylation of aryl iodides with amines to synthesize amides has been established by using SiO 2 supported Pd(0) as the catalyst in a mild basic environment (K 2 CO 3 ). This ligand-free heterogeneous reaction model can afford amide products in good to excellent yields (up to 99%) under atmospheric CO pressure and moderate temperature. The supported catalyst also displayed a broad substrate scope, good functional group tolerance and good recyclability. These feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It is also indicated that previous results relied on very high pressure (5–20 bar) of CO in the absence of a CO absorbent (Table S4, Supporting Information). 37‐40 Thus, the reactive absorption of CO by [BimH]Cl‐CuCl‐1.0ZnCl 2 can dramatically decrease the pressure and efficiently promote carbonylation reaction to obtain 70–97 yields.…”
Section: Resultsmentioning
confidence: 99%
“…It is also indicated that previous results relied on very high pressure (5–20 bar) of CO in the absence of a CO absorbent (Table S4, Supporting Information). 37‐40 Thus, the reactive absorption of CO by [BimH]Cl‐CuCl‐1.0ZnCl 2 can dramatically decrease the pressure and efficiently promote carbonylation reaction to obtain 70–97 yields.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization data for arylsilanes and amides products have been previously reported. ,,, All arylsilanes were compared with literature data: trimethoxy­( p -tolyl)­silane, trimethoxy­(4-methoxyphenyl)­silane, (4-fluorophenyl)­trimethoxysilane, (4-chlorophenyl)­trimethoxysilane, (4-bromophenyl)­trimethoxysilane, trimethoxy­( m -tolyl)­silane, trimethoxy­(3-methoxyphenyl)­silane, (3-fluorophenyl)­trimethoxysilane, (3-chlorophenyl)­trimethoxysilane, (3,5-dimethylphenyl)­trimethoxysilane, trimethoxy­(naphthalen-2-yl)­silane…”
Section: Methodsmentioning
confidence: 99%
“…[44d-e] In a related work, ligand free Pd(0)/SiO 2 catalyzed aminocarbonylation in presence of atmospheric CO has been developed by Yuan and co-workers (Scheme 26). [45] The catalyst displayed good recyclability and can be applied for synthesis of diverse array of substituted amides. However, very low yields were obtained when alkyl amines were utilized as amine source.…”
Section: Supported Palladium Catalysts In Aminocarbonylationmentioning
confidence: 99%